Li I LINE λ 460.3 nm IN SPECTRA OF SUPER LITHIUM-RICH CARBON STARS - Yakovina, L.; Pavlenko, Ya. (Одеські астрономічні публікації, 2017)
Subordinate Li I line λ 460.3 nm is quite strong and sensitive on lithium abundances at log N(Li) =3–5 that are typical in atmospheres of super lithium-rich AGB giants. However, this line cannot be a good indicator of lithium abundances due to severe blending, especially by line Fe I λ 460.294 nm. On the other hand, a sensitivity of calculated blend containing Li I line λ 460.3 nm on log N(Li) increases for more complete system of continuum opacity sources in the blue and if se this indicator for metal-deficient stars.